Pyrazinoic acid, the active form of the anti-tuberculosis drug pyrazinamide, and aromatic carboxylic acid analogs are protonophores - Fontes, Fabio L.; Rooker, Steven A.; Lynn-Barbe, Jamie K.; Lyons, Michael A.; Crans, Debbie C.; Crick, Dean C. (Frontiers in Molecular Biosciences, 2024)
Pyrazinoic acid is the active form of pyrazinamide, a first-line antibiotic used to treat Mycobacterium tuberculosis infections. However, the mechanism of action of pyrazinoic acid remains subject to debate and alternatives to pyrazinamide in cases of resistance are not available. The work presented here demonstrates that pyrazinoic acid and known protonophores including salicylic acid, benzoic acid and carbonyl cyanide m-chlorophenyl hydrazone all exhibit pH dependent inhibition of mycobacterial growth activity over a physiologically relevant range of pH values. Other anti-tubercular drugs, including rifampin, isoniazid, bedaquiline and p-aminosalicylic acid, do not exhibit similar pH-dependent growth inhibitory activities. The growth inhibition curves of pyrazinoic, salicylic, benzoic and picolinic acids, as well as carbonyl cyanide m-chlorophenyl hydrazone all fit a quantitative structure-activity relationship (QSAR) derived from acid-base equilibria with R 2 values > 0.95. The QSAR model indicates that growth inhibition relies solely on the concentration of the protonated forms of these weak acids (rather than the deprotonated forms). Moreover, pyrazinoic acid, salicylic acid and carbonyl cyanide m-chlorophenyl hydrazone all caused acidification of the mycobacterial cytoplasm at concentrations that inhibit bacterial growth. Thus, it is concluded that pyrazinoic acid acts as an uncoupler of oxidative phosphorylation and that disruption of proton motive force is the primary mechanism of action of pyrazinoic acid rather than inhibition of a classic enzyme activity.